Gerçekliği Farklı Düzlemlerde Geri Kazanmak: Eleştirel Realizm / Regaining Reality on Different Platforms: Critical Realism - Yücedağ, İbrahim; Sarsılmaz, Fidan (Journal of History Culture and Art Research, 2018)
Abstract In discussions over the natural existence of what has been communally described, the issue of how this existence is reached is among the basic problems of social theory. The main objective in the mutual understanding of commonality forms the central argument of social theory, over which there is a pursuit of order. Especially with the emphasis that he has made on different layers of reality – actual, real, and empirical – Bhaskar, who objects to the errors of voluntarism and reification in social theory, suggests a naturalistic model by emphasizing the model of thoughtful action. Bhaskar does not refute realism but plasticizes it with a new theoretic perspective, and he opens the discussion of the limits of the possibilities of naturalism. In this study, the effort with which Roy Bhaskar again tried to prioritize epistemology and ontology on an equal level and that he defined as critical realism is attempted to be understood. Öz Toplumsal olarak tanımlananın neliği üzerine yapılan tartışmalarda bu neliğe nasıl ulaşılacağı meselesi sosyal teorinin temel problemlerindendir. Özellikle sosyal teorinin ilk dönemi için merkezi konunun bir düzen arayışı olduğu bilinmektedir. Özellikle gerçekliğin farklı katmanlarına yaptığı vurguyla -aktüel, reel ve ampirik- sosyal teorideki iradecilik ve şeyleştirme hatalarına karşı çıkan Bhaskar, düşünümsel eylem modelini öne çıkararak natüralist bir model önerir. Realizmi reddedetmeyerek ancak eleştirel bir mahiyette elden geçirerek yeni bir teorik perspektifle yoğuran Bhaskar, natüralizmin olanaklılığının sınırlarını eleştirel realizmle yeniden tartışmaya açar. Bu çalışmada da Roy Bhaskar’ın epistemoloji ile ontolojiyi yeniden eşit düzeyde öncelemeye çalıştığı ve eleştirel realizm olarak tanımladığı çaba anlaşılmaya çalışılacaktır.